2017
DOI: 10.1111/jvim.14737
|View full text |Cite
|
Sign up to set email alerts
|

Breed, Coat Color, and Hair Length as Risk Factors for Hyperthyroidism in Cats

Abstract: BackgroundHyperthyroidism is very common in older cats, but the etiopathogenesis is poorly understood. Decreased risk of hyperthyroidism has been reported in certain colorpoint breeds, and this observation previously has been hypothesized to result from relatively greater tyrosine availability for thyroid hormone production because of limited ability to convert tyrosine to melanin pigment. However, studies investigating a potential link between coat pigmentation and risk of hyperthyroidism are limited.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…When comparing breeds, we found that mixed-breed cats were more likely to present hyperthyroidism. A higher incidence in crossbreeds has also been detected in other studies (CROSSLEY et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…When comparing breeds, we found that mixed-breed cats were more likely to present hyperthyroidism. A higher incidence in crossbreeds has also been detected in other studies (CROSSLEY et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Six cats affected by hyperthyroidism consumed wet food either exclusively or in combination with other food types. Canned wet food is rich in substances that can act as endocrine disruptors and may present inadequate iodine concentrations (CROSSLEY et al, 2017). Hence, several studies have demonstrated that cats fed canned commercial diets are more prone to develop hyperthyroidism (IKEDA et al, 2000;CROSSLEY et al, 2017;PAULELLI et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have found evidence that this contamination is greater in pop-top cans [7,18,19]. It is worth mentioning that studies in rats have demonstrated that the main route of elimination of ingested BPA is through hepatic glucuronidation [20], which is greatly reduced in cats making this animal extremely sensitive to the adverse effects of many drugs and toxins that require glucuronidation before elimination [3]. Thus, slower clearance may lead to higher-than-expected BPA blood and tissue levels in cats [7].…”
Section: Journal Of Endocrinology and Thyroid Research Discussionmentioning
confidence: 97%
“…The fact that the several variables surveyed had 95% confidence intervals extremely wide, even though not significant, emphasizes the potential importance of these factors, so that the enlargement of the sample size could help to clarify this bias. The lower mean age of the control group, as well as the higher percentage of euthyroid cats between 8 and 12 years of age, may also have been a limiting factor, since most studies point to a mean age of diagnosis of feline hyperthyroidism among 12 and 13 years [1,3,[20][21][22].…”
Section: Journal Of Endocrinology and Thyroid Research Discussionmentioning
confidence: 99%